Neonatal Intestinal Perforation—A Rare Complication of Small Bowel Hemangioma - Shukri, Nasser; Amara, Ridha; Malik, Shakeel; Taher, Hanan; Kilany, Mansour (European Journal of Pediatric Surgery Reports, 2013)
Intestinal perforation is an extremely rare complication of hemangioma of the small intestine in the neonatal period. This is a case report of a 27-days-old male infant who presented with signs and symptoms of acute intestinal obstruction. Exploratory laparotomy findings revealed intestinal perforation due to solitary hemangioma in the ileum, which led to obstruction from peritoneal reaction and adhesions. There are two reported cases in the literature presenting with ileal perforation in the pediatric age group, but only one previous report mentioned in the neonatal period. Because there are other more common causes of perforation in the neonatal period, intestinal hemangioma in spite of its rarity should be included in the differential diagnosis.
Keywords: neonate; ileal; perforation; hemangioma